2D: 4D asymmetry and gender differences in academic performance:evidence from Moscow and Manila - John V. C. Nye; Grigory Androuschak; Desirée Desierto; Garett Jones; Maria Yudkevich (University of the Philippines, School of Economics (UPSE), 2012)
Exposure to prenatal androgens affects both future behavior and life choices. However, there is still relatively limited evidence on its effects on academic performance. Moreover, the predicted effect of exposure to prenatal testosterone (T) - which is inversely correlated with the relative length of the second to fourth finger lengths (2D:4D) - would seem to have ambiguous effects on academic achievement since traits like confidence, aggressiveness, or risk-taking are not uniformly positive for success in school. We provide the first evidence of a non-linear relationship between 2D:4D and academic achievement using samples from Moscow and Manila. We find that there is a quadratic relationship between high T exposure and markers of achievement such as grades or test scores and that the optimum digit ratio for women in our sample is lower (indicating higher prenatal T) than the average. The results for men are generally insignificant for Moscow but significant for Manila showing similar non-linear effects. Our work is thus unusual in that it draws from a large sample of nearly a thousand university students in Moscow and over a hundred from Manila for whom we also have extensive information on high school test scores, family background and other potential correlates of achievement. Our work is also the first to have a large cross country comparison that includes two groups with very different ethnic compositions.
Keywords: 330; academic performance; female achievement; 2D4D ratio; Bildungsniveau; Akademiker; Frauen; Bildungsverhalten; Schulauswahl; Moskau; Russland; Manila; Philippinen